Experimental, molecular docking and molecular dynamic studies of natural products targeting overexpressed receptors in breast cancer - Taghizadeh, Mohammad Sadegh; Niazi, Ali; Moghadam, Ali; Afsharifar, Alireza (PLOS ONE, 2022)
Natural compounds are proper tools for inhibiting cancer cell proliferation. Hence, the search for these ligands of overexpressed receptors in breast cancer has been a competitive challenge recently and opens new avenues for drug discovery. In this research, we have investigated molecular interactions between natural products and overexpressed receptors in breast cancer using molecular docking and dynamic simulation approaches followed by extraction of the best ligand from Citrus limetta and developing for nanoscale encapsulation composed of soy lecithin using a sonicator machine. The encapsulation process was confirmed by DLS and TEM analyses. Anticancer activity was also examined using MTT method. Among the investigated natural compounds, hesperidin was found to bind to specific targets with stronger binding energy. The molecular dynamics results indicated that the hesperidin-MCL-1 complex is very stable at 310.15 K for 200 ns. The RP-HPLC analysis revealed that the purity of extracted hesperidin was 98.8% with a yield of 1.72%. The results of DLS and TEM showed a strong interaction between hesperidin and lecithin with an entrapped efficiency of 92.02 ± 1.08%. Finally, the cytotoxicity effect of hesperidin was increased against the MDA-MB-231 cell line with an IC50 value of 62.93 μg/mL after encapsulation, whereas no significant effect against the MCF10A cell line. We showed for the first time that hesperidin is a flexible and strong ligand for the MCL-1 receptor. Also, it has the in vitro ability to kill the MDA-MB-231 cell lines without having a significant effect on the MCF10A cell lines. Therefore, hesperidin could be used as a food ingredient to generate functional foods.